Neurotrauma investigation through spatial omics guided by mass spectrometry imaging: Target identification and clinical applications. Issue 1 (29th July 2021) - Mallah, Khalil; Zibara, Kazem; Kerbaj, Coline; Eid, Ali; Khoshman, Nour; Ousseily, Zahraa; Kobeissy, Abir; Cardon, Tristan; Cizkova, Dasa; Kobeissy, Firas; Fournier, Isabelle; Salzet, Michel
Abstract: Traumatic brain injury (TBI) represents one of the major public health concerns worldwide due to the increase in TBI incidence as a result of injuries from daily life accidents such as sports and motor vehicle transportation as well as military‐related practices. This type of central nervous system trauma is known to predispose patients to several neurological disorders such as Parkinson's disease, Alzheimer's disease, chronic trauamatic encephalopathy, and age‐related Dementia. Recently, several proteomic and lipidomic platforms have been applied on different TBI studies to investigate TBI‐related mechanisms that have broadened our understanding of its distinct neuropathological complications. In this study, we provide an updated comprehensive overview of the current knowledge and novel perspectives of the spatially resolved microproteomics and microlipidomics approaches guided by mass spectrometry imaging used in TBI studies and its applications in the neurotrauma field. In this regard, we will discuss the use of the spatially resolved microproteomics and assess the different microproteomic sampling methods such as laser capture microdissection, parafilm assisted microdissection, and liquid microjunction extraction as accurate and precise techniques in the field of neuroproteomics. Additionally, we will highlight lipid profiling applications and their prospective potentials in characterizing molecular processes involved in the field of TBI. Specifically, we will discuss the phospholipid metabolism acting as a precursor for proinflammatory molecules such as eicosanoids. Finally, we will survey the current state of spatial neuroproteomics and microproteomics applications and present the various studies highlighting their findings in these fields.